Saccharomyces cerevisiae fermentation product improves robustness of equine gut microbiome upon stress - Ganda, Erika; Chakrabarti, Anirikh; Sardi, Maria I.; Tench, Melissa; Kozlowicz, Briana K.; Norton, Sharon A.; Warren, Lori K.; Khafipour, Ehsan (Frontiers in Veterinary Science, 2023)
Nutritional and environmental stressors can disturb the gut microbiome of horses which may ultimately decrease their health and performance. We hypothesized that supplementation with a yeast-derived postbiotic (Saccharomyces cerevisiae fermentation product - SCFP) would benefit horses undergoing an established model of stress due to prolonged transportation. Quarter horses (n=20) were blocked based on sex, age (22 ± 3 mo) and body weight (439 ± 3 kg) and randomized to receive either a basal diet of 60% hay and 40% concentrate (CON) or the basal diet supplemented with 21 g/d Diamond V TruEquine C (SCFP; Diamond V, Cedar Rapids, IA) for 60 days. On day 57, horses were tethered with their heads elevated 35 cm above wither height for 12 h to induce mild upper respiratory tract inflammation. Fecal samples were collected at day 0, day 28 and day 56 before induction of stress, and at 0 h, 12 h, 24 h and 72 h post-stress and subjected to DNA extraction and Nanopore shotgun metagenomics. Within sample (alpha) diversity was evaluated by fitting a linear model and between sample (beta) diversity was tested with permutational ANOVA. The SCFP stabilized alpha diversity across all time points, whereas CON horses had more fluctuation (P < 0.05) at 12, 24 and 72 h post-challenge compared to d 56. A significant difference between CON and SCFP was observed at 0 and 12 h. There was no difference in beta-diversity between SCFP and CON on d 56. Taken together, these observations led us to conclude that treatment with SCFP resulted in more robust and stable microbial profiles in horses after stress challenge.